Smart Living Ciamis District Health Office - budiawan, arie; Syara Purnamasari; Kiki Endah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
The application of the smart living concept by the Ciamis Regency Health Office in encouraging healthy living behavior of the community, as well as structuring the ecosystem of living places that support the quality of life of the community. This study aims to analyze how the Ciamis Regency Health Office applies the smart living concept in an effort to encourage healthy living behaviors in the community. The research method uses a qualitative approach with data collection techniques of observation, in-depth interviews, and document studies of programs and policies related to the implementation of smart living. The results showed that the Ciamis Regency Health Office has implemented several information technology-based initiatives in order to encourage healthy lifestyles in the community through health information outreach and community self health monitoring applications that will be published in 2024 now. However, the integration and synchronization of cross-sectoral regulations and data related to smart living are considered still lacking and not optimal. The policy recommendations given are the need to strengthen regulations and institutions to support the implementation of smart living in the health sector in Ciamis Regency.